ICONOGRAPHY AND THE CONCEPT OF TIME IN THE HISPANIA - ROMANA MOSAIC - Abouarab, Mohamed A. R. (2015)
In this paper, the concept of iconography will be analyzed as well as its evolution up to the Hispanic Roman mosaic will be discussed. The discussion of the concept will be divided into three main parts. First, the paper will examine the history of the Roman Invasion of Hispania. Second, the concept of time in Rome will be investigated. Finally, the concept of iconography in time and the evolution of mosaic in Hispania will be discussed.